EKSPLORASI TUMBUHAN OBAT PADA TAMAN NASIONAL GUNUNG LEUSER, RESORT SEI BETUNG, SUMATERA UTARA - Khairul Ambri; Yunus Afifuddin; Aswita Hafni (Peronema Forestry Science Journal, 2015)
Medicinal plants have a very important role for world health that need to be done of research to analyze the diversity of medicinal plants. Medicinal plants exploratory research had been done in the Gunung Leuser National Park, Sei Betung Resort from Juny to Agustus 2014. Medicinal plant species are known to be recorded and identified. The results of the identification of medicinal plants has been done in Gunung Leuser National Park, Sei Betung Resort  found as many as 27 types of medicinal plants.The dominant species is Melastoma malabathricum. The diversity of medicinal plants in the  Gunung Leuser National Park, Sei Betung Resort Hutan classified as moderate. Keywords: Medical plants, Gunung Leuser National Park and Diversity of plants